2010
DOI: 10.1002/dev.20482
|View full text |Cite
|
Sign up to set email alerts
|

Rodent model of infant attachment learning and stress

Abstract: Here we review the neurobiology of infant odor learning in rats, and discuss the unique role of the stress hormone corticosterone (CORT) in the learning necessary for the developing rat. During the first 9 postnatal (PN) days, infants readily learn odor preferences, while aversion and fear learning are attenuated. Such restricted learning may ensure that pups only approach their mother. This sensitive period of preference learning overlaps with the stress hyporesponsive period (SHRP, PN4–14) when pups have a r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
90
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 113 publications
(95 citation statements)
references
References 121 publications
(160 reference statements)
5
90
0
Order By: Relevance
“…These include associative odor preference learning following classical conditioning, which occurs in rats less than ϳP10 -12 (Moriceau et al 2010;Wilson and Sullivan 1994). Certainly, there are similarities across systems, as our circuit-level changes (in rats ϽP14) roughly matched in time frame.…”
Section: Discussionmentioning
confidence: 94%
“…These include associative odor preference learning following classical conditioning, which occurs in rats less than ϳP10 -12 (Moriceau et al 2010;Wilson and Sullivan 1994). Certainly, there are similarities across systems, as our circuit-level changes (in rats ϽP14) roughly matched in time frame.…”
Section: Discussionmentioning
confidence: 94%
“…As described earlier, rodent studies have found that maternal absence may accelerate amygdala functional development (Callaghan & Richardson, 2011Moriceau, et al, 2004;Moriceau, Roth, & Sullivan, 2010). It is not possible to interpret, based on the data described in humans above, whether humans also experience amygdala accelerations in functional development (discussed in Gee, et al, in press).…”
Section: Human Amygdala Following Early Caregiver Deprivationmentioning
confidence: 94%
“…Specifically, using a procedure that readily causes threat/fear learning in children and myriad other species, which involves pairing a neutral stimulus (i.e., light, tone, smell) with pain (i.e., mild-moderate electric shocks, a piercing load noise or a painful pinch), infants rapidly learned aversion/defense responses to the previously neutral sound or smell. The amygdala is critically important for this learning (Fanselow & Gale, 2003;Fanselow & LeDoux, 1999;Johansen, Cain, Ostroff, & LeDoux, 2011;Maren, 2003;Moriceau, Roth, & Sullivan, 2010). It should be noted that infants' failure to learn about pain is not due to the failure to detect pain since both human and rodent infant have functional pain systems, however they are lacking the neural circuitry to support amygdala-dependent fear learning (Barr, 1995;Fitzgerald, 2005;Graham et al, 2016;Tottenham, 2012).…”
Section: The Attachment Figure Guides Learning About the Worldmentioning
confidence: 99%